The Effectiveness of Compassion-Focused Group Counseling with Imagery and Chair Work Techniques to Increase Students’ Self-Esteem - Sopian, Asep Amat; Wibowo, Mungin Eddy; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2023)
Self-esteem is significant for an individual’s life due to its ability to direct oneself in valuing something, deciding proper attitudes towards different interpersonal relationships, and motivating the development of self-potential. Regarding this urgency, the present study attempted to examine the effectiveness of compassion-focused group counseling using imagery and chair work techniques to increase the self-esteem of students at SMP IT Al-Multazam 2, Kuningan. It was an experimental research taht used a randomized pretest-posttest comparison group design. Here, 12 students were randomly selected using a purposive sampling technique from 72 students whose self-esteem was low. They were further grouped into two experimental groups. Based on the results of Wilcoxon and Mann Whitney tests, the compassion-focused group counseling with imagery and chair work techniques has been effective to increase students’ self-esteem. Moreover, the study implications, findings, and discussion are deeply explained in the discussion section.